2007
DOI: 10.1677/joe-07-0056
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prenatal exposure to the endocrine disruptor bisphenol A on mammary gland morphology and gene expression signature

Abstract: Bisphenol A (BPA), known as an environmental endocrine disruptor, is widely used as a plasticizer. This study aims to investigate whether exposure in utero to BPA alters the architecture, proliferative index, and genomic signature of the rat mammary gland during critical stages of development. Pregnant rats were gavaged with 25 mg BPA/kg body weight (BW; low-dose group) or 250 mg BPA/kg BW (high-dose group) from day 10 post-conception to delivery. Female litters were euthanized at 21, 35, 50, and 100 days, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
99
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(106 citation statements)
references
References 76 publications
4
99
0
Order By: Relevance
“…Furthermore, rats exposed to BPA in utero developed precancerous and cancerous lesions (32). Also, perinatal exposure increased rodents' sensitivity to chemical carcinogens (33)(34)(35)(36). Although a small human study found no association between To whom correspondence should be addressed.…”
mentioning
confidence: 99%
“…Furthermore, rats exposed to BPA in utero developed precancerous and cancerous lesions (32). Also, perinatal exposure increased rodents' sensitivity to chemical carcinogens (33)(34)(35)(36). Although a small human study found no association between To whom correspondence should be addressed.…”
mentioning
confidence: 99%
“…In rats high-dose BPA exposure induced changes in genes related to differentiation suggesting alterations in the normal development of the gland. The increase of undifferentiated structures and the changes in the gene expression profile at different ages suggested that prenatal exposure to BPA can affect the susceptibility of the mammary gland to transformation [131]. Gestational exposure to the estrogen-mimic BPA also altered the developing mammary glands of rhesus monkey female in a comparable manner to that observed in rodents [132].…”
Section: Bisphenol Amentioning
confidence: 81%
“…Moreover, BBP induced geneomic changes in rat mammary gland after neonatal/prepubertal exposure (post-natal days 2-20) [155]. The increase of undifferentiated structures and the changes in the gene expression profile at different ages suggested that prenatal exposure to BPA can affect the susceptibility of the mammary gland to transformation [131].…”
Section: Phthalatesmentioning
confidence: 96%
“…This contamination is due to persistent pollution. The exposure through breastfeeding can affect the health of children in the early stages of growth [13, 14, 60]. …”
Section: Xenoestrogensmentioning
confidence: 99%